2017
DOI: 10.18632/oncotarget.17601
|View full text |Cite
|
Sign up to set email alerts
|

UBE2J2 promotes hepatocellular carcinoma cell epithelial-mesenchymal transition and invasionin vitro

Abstract: Ubiquitin-conjugating enzyme E2 J2 (UBE2J2) is an ubiquitin proteasome component that responds to proteotoxic stress. We found that UBE2J2 was highly expressed in cellular protrusions of HCCLM3 metastatic hepatocellular carcinoma (HC) cells. Immunohistochemical analyses showed that UBE2J2 was expressed at higher levels in HC patient tissues than in corresponding non-tumor tissues. Because cellular protrusions are important for cell invasion, we hypothesized that UBE2J2 promotes HC cell invasion. We used chip-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…We could not find information in the literature regarding UBE2J2 expression in EPN. However, Chen et al [ 119 ] reported higher expression of UBE2J2 protein in hepatocellular carcinoma compared to normal liver tissue, which was associated with increased epithelial to mesenchymal transition (EMT) in vitro, whereas UBE2J2 gene knockdown promoted EGFR expression [ 119 ]. UBE4B regulates the degradation of the tumor suppressor p53 in breast cancer [ 120 ] and UBE2Q1 has been proposed as a marker for high-grade serous ovarian cancer [ 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…We could not find information in the literature regarding UBE2J2 expression in EPN. However, Chen et al [ 119 ] reported higher expression of UBE2J2 protein in hepatocellular carcinoma compared to normal liver tissue, which was associated with increased epithelial to mesenchymal transition (EMT) in vitro, whereas UBE2J2 gene knockdown promoted EGFR expression [ 119 ]. UBE4B regulates the degradation of the tumor suppressor p53 in breast cancer [ 120 ] and UBE2Q1 has been proposed as a marker for high-grade serous ovarian cancer [ 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…E2 family members are associated with various diseases including cancers, muscular atrophy, Parkinson's disease, Fanconi anemia and development disorders 114–116 . Among the ERAD related E2 enzymes, UBE2J2 expression profiles are associated with hepatocellular carcinoma 117 . Although neither UBE2J1 nor UBE2G2 is linked to any disease yet, the depletion of UBE2J1 in a mouse model displayed impaired spermatid development profile 91 .…”
Section: Human Phenotypes and Animal And Cellular Disease Models Asso...mentioning
confidence: 99%
“…[114][115][116] Among the ERAD related E2 enzymes, UBE2J2 expression profiles are associated with hepatocellular carcinoma. 117 Although neither UBE2J1 nor UBE2G2 is linked to any disease yet, the depletion of UBE2J1 in a mouse model displayed impaired spermatid development profile. 91 Although these members are well involved in the ERAD machinery, the knockout HEK293 and HeLa cell models were designed to comprehend their physiological functions rather than their participation in ERAD.…”
Section: E2 Ubiquitin Conjugating Enzymesmentioning
confidence: 99%
“…UBE2J2 is involved in cancer cell invasion. Accordingly, overexpression of UBE2J2 has been detected in cell protrusions of HCCLM3 hepatocellular carcinoma cells [80]. However, further studies are required to understand the specific role(s) of UBE2J2 in promoting cancer progression.…”
Section: Ube2j2 In Cancermentioning
confidence: 99%